Factors Influencing Performance of Applied Research: Evidence from the Higher Education Institutions in the Kurdistan Region of Iraq - Mohammed, Shlair; Mohammed, Rezgar; Rasol, Snobar; Kachal, Edi (Humanities Journal of University of Zakho, 2022)
Knowing what influences researchers on conducting applied research in developing countries is of interest to policymakers in higher education institutions. This study utilized a quantitative approach to investigate factors that drive academics in the higher education institutions in the Kurdistan Region of Iraq on conducting applied research. For this purpose, data were collected using a survey from researchers at different universities and fields and then were analyzed using the probit model. Based on the main findings of this study, the probability of conducting applied research increases as the years of experience increase when a researcher has external funding, while the probability decreases as the years of experience increase when a researcher has only the knowledge of applying to external funding without actually having any funding available. This study recommends some actions that help in promoting the research field in the higher education institutions in the Kurdistan Region of Iraq.